Metallic Implant Surface Activation through Electrospinning Coating of Nanocomposite Fiber for Bone Regeneration - Al-Khateeb, Amjed; Al-Hassani, Emad S.; Jabur, Akram R. (International Journal of Biomaterials, 2023)
There is a critical need in orthopedic and orthodontic clinics for enhanced implant-bone interface contact to facilitate the quick establishment of a strong and durable connection. Surface modification by bioactive multifunctional materials is a possible way to overcome the poor osteoconductivity and the potential infection of Ti-based implants. Ti-25Zr biometallic alloy was prepared by powder metallurgy technique and then coated by Nano-composite fiber using electrospinning. Ceramic Nanocompound (CaTiO3, BaTiO3) was used as filler material and individually added to polymeric matrices constructed from the blend of polycaprolactone/chitosan. Using optical microscopy, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), and wettability, respectively, the morphology, chemical analysis, surface roughness, and contact angle measurements of the samples were evaluated. The result shows a significant improvement in cell viability, proliferation, and ALP activity for coated samples compared to noncoated samples. PCL/Chitosan/Nano-CaTiO3 (CA1) recorded remarkable enhancement from the surface-coated samples, demonstrating a significantly higher cell viability value after seven days of MC3T3-E1 cell culture, reaching 271.56 ± 13.15%, and better cell differentiation with ALP activity reaching 5.61 ± 0.35 fold change for the same culture time. PCL/Chitosan/Nano-BaTiO3 (BA1) also shows significant improvement in cell viability by 181.63 ± 17.87% and has ALP activity of 3.97 ± 0.67 fold change. For coated samples, cell proliferation likewise exhibits a considerable temporal increase; the improvement reaches 237.53% for (CA1) and 125.16% for (BA1) in comparison with uncoated samples (bare Ti-25Zr). The coated samples resist bacteria in the antibacterial test compared to the noncoated samples with no inhibition zone. This behavior suggests that a Nanocomposite fiber coat containing an active ceramic Nanocompound (CaTiO3, BaTiO3) promotes cell growth and holds promise for orthodontic and orthopedic bioapplication.